The role of the primary care outpatient clinic in the promotion of healthy nutrition – preliminary reports - Dudzińska, Marta; Neć, Monika; Zwolak, Agnieszka; Oszywa-Chabros, Anna; Malicka, Joanna; Smoleń, Agata; Daniluk, Jadwiga; Tarach, Jerzy S. (Family Medicine & Primary Care Review, 2016)
Background. Understanding the principles of prophylaxis, and awareness of the importance of proper nutrition in maintaining wellbeing should be a part of every doctor–patient relationship. Objectives . An evaluation of the sources of knowledge and access to information about healthy nutrition in primary care outpatient clinics. Material and methods . The study comprised 222 subjects (150 women and 72 men) aged 18–87 years (median 47.5). The study used a self-prepared questionnaire. Results . 97.7% of the patients (n = 217) were aware of the impact of diet on health, of which only 9.9% (n = 22) knew the rules of healthy nutrition well, 55.4% (n = 123) had knowledge at a medium level, and 31.1% (n = 69) at a low level. Dietary mistakes were more frequently reported by men (p = 0.001), and lack of time (38.2%; n = 85) and knowledge (29.3%; n = 65) were reported as the main reasons. The Internet (64.9%; n = 144) is the main source of knowledge about healthy nutrition. It is used mainly by younger people (78.9% < 50 years; n = 97 vs. 47.5% ≥ 50 years; n = 47; p < 0.001). People ≥ 50 years prefer to talk with a doctor (22.2%; n = 22 vs. 4.9%; n = 6; p < 0.001). Patients expect to get dietary education in their primary care outpatient clinic in the form of leaflets (58.6%; n = 130), posters (25.7%; n = 57), conversation with a doctor (36.9%; n = 82), and consultation with a nutritionist (33.3%; n = 74). Significantly more women want to get information directly from a doctor (p = 0.01). Conclusions . The primary care outpatient clinic is an important source of information on healthy nutrition. Patients expect access to information in the form of leaflets and medical or dietary consultations conducted in a family doctor’s practice. We should consider the implementation of educational programmes on the principles of healthy nutrition in primary care outpatient clinics.